Uniaxial cell stretching device for live-cell imaging of mechanosensitive cellular functions - Shao, Yue (AIP Publishing LLC, 2013)
External mechanical stretch plays an important role in regulating cellular behaviors through intracellular mechanosensitive and mechanotransductive machineries such as the F-actin cytoskeleton (CSK) structures and focal adhesions (FAs) anchoring the F-actin CSK to the extracellular environment. Studying the mechanoresponsive behaviors of the F-actin CSK and FAs in response to cell stretch has great importance for further understanding mechanotransduction and mechanobiology. In this work, we developed a novel cell stretching device combining dynamic directional cell stretch with in situ subcellular live-cell imaging. Using a cam and follower mechanism and applying a standard mathematical model for cam design, we generated different dynamic stretch outputs. By examining stretch-mediated FA dynamics under step-function static stretch and the realignment of cell morphology and the F-actin CSK under cyclic stretch, we demonstrated successful applications of our cell stretching device for mechanobiology studies where external stretch plays an important role in regulating subcellular molecular dynamics and cellular phenotypes.